2014
DOI: 10.1021/ja506261t
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal Synthesis of 1T-WS2 and 2H-WS2 Nanosheets: Applications for Photocatalytic Hydrogen Evolution

Abstract: In recent years, a lot of attention has been devoted to monolayer materials, in particular to transition-metal dichalcogenides (TMDCs). While their growth on a substrate and their exfoliation are well developed, the colloidal synthesis of monolayers in solution remains challenging. This paper describes the development of synthetic protocols for producing colloidal WS2 monolayers, presenting not only the usual semiconducting prismatic 2H-WS2 structure but also the less common distorted octahedral 1T-WS2 structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

44
584
1
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 713 publications
(661 citation statements)
references
References 56 publications
44
584
1
1
Order By: Relevance
“…[ 14 ] It has been observed that the components of the 1T phase in the high-resolution W4f spectrum appear at binding energies about 1 eV lower than those belonging to the 2H phase. [ 18 ] Figure 2 shows high-resolution XPS spectrum of W4f for WS 2 in the bulk state and after exfoliation. It is clear that the material experienced a signifi cant phase transition upon exfoliation presenting the components of the metallic 1T phase (at ≈32 and 34 eV) more prominent than those of the 2H phase (at ≈33 and 35 eV).…”
Section: Resultsmentioning
confidence: 99%
“…[ 14 ] It has been observed that the components of the 1T phase in the high-resolution W4f spectrum appear at binding energies about 1 eV lower than those belonging to the 2H phase. [ 18 ] Figure 2 shows high-resolution XPS spectrum of W4f for WS 2 in the bulk state and after exfoliation. It is clear that the material experienced a signifi cant phase transition upon exfoliation presenting the components of the metallic 1T phase (at ≈32 and 34 eV) more prominent than those of the 2H phase (at ≈33 and 35 eV).…”
Section: Resultsmentioning
confidence: 99%
“…Semiconductor photocatalyst systems can be used to split water into H 2 and O 2 , to photo‐reduce CO 2 into renewable fuels such as CH 3 OH, CH 4 , and CO, and to decompose various organic contaminations to remedy the environment. These methods use solar energy as the source of photons to promote reactions 1, 2. Photocatalytic reaction processes primarily involve three main steps: (1) the photogeneration of electron–hole pairs through the absorption of solar light of the energy larger than the band gap of photocatalyst, (2) the charge separation and migration onto the surface without recombination, and (3) the reduction/oxidation reaction on the surface of photocatalyst 3, 4, 5.…”
Section: Introductionmentioning
confidence: 99%
“…1 nm [11], (c) adapted with permission from Mahler et al [54] and (d-g) adapted with permission from Yoo et al [55].…”
mentioning
confidence: 99%
“…2H-WS 2 forms instead of 1T-WS 2 when hexamethyldisilazane (HMDS) is added to oleylamine [54]. Figure 5c shows the low-and high-resolution TEM images of 1T-and 2H-WS 2 monolayers formed in the absence and presence of HMDS, respectively.…”
mentioning
confidence: 99%